Uji Performa Mesin Bensin dengan Sistem Injeksi Berbahan Bakar HCNG - Sasongko, Mega Nur; Zuhri, Abdi Afifuddin (Jurnal Rekayasa Mesin, 2021)
Compressed Natural Gas (CNG) is an alternative renewable fuel gasoline replacement. However, due to the low heating value, the use of CNG in the engine will reduce its performance. The addition of hydrogen gas in CNG namely hydrogen-enriched compressed natural gas is expected to increase the power of the motor. This study aims to analyze the effect of hydrogen concentration on the performance of a CNG gasoline engine. The research was conducted on the engine with an indirect fuel injection system with a volume of 124,9 cc. The parameter of the engine that measured is torque, effective power, specific fuel consumption, and effective thermal efficiency. The results showed that the small percentage of hydrogen in CNG could increase the power of the gasoline engine. Power and efficiency reach a maximum of 10% hydrogen concentration. Increasing the proportion of hydrogen in CNG fuel above 10% will significantly reduce engine torque and power. Engine performance at optimal conditions with 10% hydrogen results in torque of 2.71 Kg.m at 670 rpm, effective power of 3.28 Ps at 1055 rpm, SFCe 0.17 Kg / Ps. Hours at 770 rpm and 33.62% effective thermal efficiency at 770 rpm